A study of English blends: From structure to meaning and back again. (April 2014) - Beliaeva, Natalia
<x xml:space="preserve">Abstract</x> This article presents an approach to the resolution of the much discussed problem of morphological classification of blend words and their distinction from such neighbouring morphological categories as clipping compounds. The research focuses on novel coinages and takes a data-driven approach to study the interaction between the form and the meaning of blends/clipping compounds. A multifactorial analysis of formal and semantic properties of these words is undertaken, as a result of which phonological and structural differences between blends and clipping compounds are explained using formal and semantic factors.